Fire and Rescue Boat Design in Tanjung Perak Waters - Aldrin Ferdiansyah; Erivife Pranatal (WAVE: Jurnal Ilmiah Teknologi Maritim, 2024)
Tanjung Perak is the name of a port located on Jalan Jamrud Utara, Perak Utara, Pabean Cantian District, Surabaya, East Java, 60165. Geographically, Tanjung Perak port is located between 112°-30’-13’’ East Longitude and 07°-70’-30’’ South Latitude, precisely in the Madura Strait, North of Surabaya. The number of ships passing through Tanjung Perak waters is very large so the number of ships passing increases the potential for accidents. It is conducted to minimize ship accidents that cause fatalities or losses. Shipbuilding in the maritime world involves stages ranging from determining ship geometry, conducting resistance and stability analysis, and designing effective propulsion systems. In addition, ship design must also consider variables such as line plan which focuses on the physical aspects and hydrodynamic performance of the ship, while general arrangement focuses on the internal organization and function of the ship. Other safety support facilities are Life Buoy, Life Jacket and complete firefighter safety clothing. The researcher obtained the main dimensions with a ship length of 7.5 meters, width of 2 meters, height of 1.6 meters, draft of 0.5 meters, and speed of V 8 Knots. The ship is equipped with a water pump with a flow rate of 199 meters/minute or 3.316 meters/second. The ship has a specific speed of 157rpm which functions to extinguish fires when a fire occurs on the ship.